2022
DOI: 10.3390/s22218130
|View full text |Cite
|
Sign up to set email alerts
|

Design and Verification of an Integrated Panoramic Sun Sensor atop a Small Spherical Satellite

Abstract: This paper proposes an integrated panoramic sun sensor (IPSS) for the small spherical satellite Q-SAT that has been working in orbit since 2020. IPSS is essentially a set of temperature-compensated photoelectric cells distributed on the spherical surface of Q-SAT. Compared with traditional sun sensors, IPSS has full spherical coverage of 4π so that the sun vector from any direction can be inversed. The mechatronic design and mathematical model of the proposed IPSS are presented. In-depth error analyses in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Results show that the orientation accuracy from sun measurement is better than 9" (3σ), and the attitude accuracy from star measurement is better than 5" (3σ) for pointing and 11" (3σ) for rolling respectively. Existing conventional sun sensors have the highest accuracy up to about 0.01° [44]. It can be seen that while maintaining the high-precision stars measurement function, the integrated sensor also has the ability to measure the sun in the daytime, and the accuracy is significantly better than the existing camera-based sun sensors.…”
Section: A Discussion and Conclusionmentioning
confidence: 99%
“…Results show that the orientation accuracy from sun measurement is better than 9" (3σ), and the attitude accuracy from star measurement is better than 5" (3σ) for pointing and 11" (3σ) for rolling respectively. Existing conventional sun sensors have the highest accuracy up to about 0.01° [44]. It can be seen that while maintaining the high-precision stars measurement function, the integrated sensor also has the ability to measure the sun in the daytime, and the accuracy is significantly better than the existing camera-based sun sensors.…”
Section: A Discussion and Conclusionmentioning
confidence: 99%
“…Several studies have reported such a reduction in photovoltaic conversion efficiency with the angle, which has been referred to as angular loss or Kelly cosine characteristics [26,[35][36][37][38][39]. Angular loss typically occurs when the radiation incidence angle surpasses about 47.5 • , diminishing to zero beyond 80 • [40]. The photovoltaic conversion efficiency decay factor (PCEDF) µ is introduced to correct the impact of the radiation incidence angle on the photovoltaic conversion efficiency of the solar cells, and the solar radiation incidence angle θ in determines its value, as follows:…”
Section: Angular Loss Correctionmentioning
confidence: 99%